Radicalism in Political Perspective and Peace Education - Roce Marsaulina (GoAcademica Research & Publishing, 2021)
The international community is facing the same global situation and conditions for crimes against humanity that have occurred in decades, namely the radicalism movement and international terrorism. Indonesia, as the largest country in Southeast Asia, has experienced toughening of the radicalism movement based on religion as its basic reference. Moreover, the international terrorism movement Al Qaeda and the ISIS Group (Islamic State in Iraq and Syria) have become the mecca for the radicalism movement in Indonesia. How can Indonesia face the radicalism movement, what should Indonesia do and what is the solution so that Indonesia can be minimized from the crimes of radicalism and the global terrorism movement? This is what is discussed in this article. In Indonesia, the radicalism movement not only begins from thoughts based on religious teachings but also the political, ideological and enthusiastic elements of certain groups with different views and directions. In this article, the discussion begins with how religion responds to views about radicalism and radicalism movements, especially those that occur in Indonesia, a pluralistic country with various ethnic groups, various languages, cultural and religious traditions. Indonesia is a country with Pancasila as its state ideology. Apart from Religious Education which teaches how to live amongst fellow Indonesian citizens, to respect each other and respect differences, Indonesia also has the Bhineka Tunggal Ika (Unity in Diversity) as its national motto which reinforces the Pancasila philosophy, with life’s view and freedom to embrace the religion one believes in.